2012
DOI: 10.1038/jcbfm.2012.189
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation after Subarachnoid Hemorrhage: Comparison of Three Methods

Abstract: In patients after subarachnoid hemorrhage (SAH) failure of cerebral autoregulation is associated with delayed cerebral ischemia (DCI). Various methods of assessing autoregulation are available, but their predictive values remain unknown. We characterize the relationship between different indices of autoregulation. Patients with SAH within 5 days were included in a prospective study. The relationship between three indices of autoregulation was analyzed: two indices calculated using spontaneous blood pressure fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 44 publications
(99 reference statements)
2
57
0
Order By: Relevance
“…Thus, some authors were able to detect good agreement between different measurement methods [46], the majority of previous studies demonstrated only minor correlations [8,10,47]. However, specificity for predicting DCI could be enhanced by combining stimulus-response and spontaneous fluctuation methods obtained from the same patient, although the time courses of the two indices showed only a weak correlation [9].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, some authors were able to detect good agreement between different measurement methods [46], the majority of previous studies demonstrated only minor correlations [8,10,47]. However, specificity for predicting DCI could be enhanced by combining stimulus-response and spontaneous fluctuation methods obtained from the same patient, although the time courses of the two indices showed only a weak correlation [9].…”
Section: Discussionmentioning
confidence: 95%
“…With this test, the autoregulation index (ARI) is measured which is derived from reactions of the middle cerebral artery flow velocity to blood pressure variations induced by bilateral thigh cuff deflations [7]. However, validity of those different CA measurements remains unclear since previous studies demonstrated only a very limited consistency between those methods [8][9][10][11]. This implicates that these methods are not interchangeable when describing the actual status of CA.…”
Section: Introductionmentioning
confidence: 99%
“…An appropriate explanation for this phenomenon might also be a direct mechanism-e.g., mediated chemically through hemoglobin metabolites or physically through pressure changes-which inflicts the intraparenchymal microglia accumulation. Another possible explanation for asymmetric microglia accumulation after SAH has been discussed by Czosnyka and co-workers, who argue for an asymmetry of blood flow auto-regulation after SAH [12].…”
Section: Tktk+mentioning
confidence: 94%
“…Moreover, investigations combining near infrared spectroscopy derived cortical oxygenation and transcranial Doppler derived middle cerebral artery Fv also indicate a cortical vulnerability. Budohoski et al 34 found that the correlation between ABP and Fv seems to be lower than the correlation between ABP and NIRS oxygenation, while Kuriyama 35 demonstrated that prior to the onset of syncope, cortical oxygenation decreases, while middle cerebral artery Fv remains constant. From a teleological point of view, such cortical sensitivity to high ICP could be a mechanism for diverting blood flow to areas of the brain most crucial for survival; the brainstem cardiorespiratory nuclei.…”
Section: Differential Control Of Cortical Compared To Global Blood Flowmentioning
confidence: 99%